2019
DOI: 10.1039/c9cc03906f
|View full text |Cite
|
Sign up to set email alerts
|

Extra hydrogen bonding interactions by peripheral indole groups stabilize benzene-1,3,5-tricarboxamide helical assemblies

Abstract: The indole groups (Ind) of these BTA monomers provide an additional hydrogen bonding interaction that enables the formation of remarkably stable supramolecular helices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…BTA-based molecules are traditionally depicted as perfectly C3-symmetrical units; however, analysis of the available crystalline BTA-based molecule structure provides evidence that even the amide groups of BTA do not necessarily retain C3 symmetry in three-dimensional space (relative to the BTA ring). [48][49][50][51][52] The molecule can be distorted from flat and C3 symmetrical, which can be further enhanced by substituent flexibility; however, the hydrogen bond network between the BTA amide groups remains unperturbed.…”
Section: Proposed Mechanism Of Higher-order Interfiber Interactionsmentioning
confidence: 99%
“…BTA-based molecules are traditionally depicted as perfectly C3-symmetrical units; however, analysis of the available crystalline BTA-based molecule structure provides evidence that even the amide groups of BTA do not necessarily retain C3 symmetry in three-dimensional space (relative to the BTA ring). [48][49][50][51][52] The molecule can be distorted from flat and C3 symmetrical, which can be further enhanced by substituent flexibility; however, the hydrogen bond network between the BTA amide groups remains unperturbed.…”
Section: Proposed Mechanism Of Higher-order Interfiber Interactionsmentioning
confidence: 99%
“…The flexibility of the side-chains present in BTA Gly monomers allows a range of energetically close conformations to be accessible in the dimeric state. Such conformations have not been detected in the case of other ester BTA monomers, [57][58][59]62 highlighting the richness of the structures accessible by simple modulation of the group connected to the amide  carbon. The co-assembly of monomers of different nature constitutes the next step for the construction of intricate functional supramolecular architectures.…”
Section: Discussionmentioning
confidence: 95%
“…44 Moreover, mixing different types of BTA monomers has recently emerged as a remarkable method to control the chirality and structure of helical co-assemblies [45][46][47][48] and construct elaborate functional supramolecular materials. 37-39, 41, 49 Deriving BTA monomers by grafting -amino esters (ester BTAs, Chart 1b) [50][51][52][53][54][55][56][57][58][59][60][61][62] is an appealing strategy to modulate the nature of groups and functions attached to the amide functions. Previous studies have revealed that the nature of the self-assemblies formed by ester BTAs is strongly dependent on the nature and stereochemistry of the group (R 1 in Chart 1b) located next to the amide function as well as on experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…11C). 172 Small-Angle Neutron Scattering experiments revealed long and rigid one-dimensional cylinders with L > 1000 Å and DP w > 275, and circular dichroism showed intense signals that originate from the chiral nanoscale organization of the supramolecular polymers (Fig. 11D).…”
Section: Effect Of Peptides On the Supramolecular Polymerization Of Aromaticsmentioning
confidence: 99%